TO APPLICATION OF BIO-GAS UNITS: ORGANIZATIONAL AND TECHNOLOGICAL MODEL - Thuy Nga Nguyen (Наука и техника)
Analysis of the published papers written by national and foreign researchers reveals that an increasing global energy deficit, exhaustion of  fossil organic and nuclear fuels, chemical and radio-active contamination of the environment are main reasons in favour of  thorough investigation  and wide introduction of non-conventional and renewable energy sources. Nowadays Vietnamese Institute of Energy Science has been developing the state-of-the-art bio-gas technologies on the  basis of application and modernization of Chinese and Dutch family-style technologies. The most rational technologies are combined ones which operate using various types of energy raw materials, for example, solar and bio-gas energy because usage of solar energy expands operational possibilities of the bio-gas system, ensures its operation within wide temperature range creating necessary parameters for the required technological task.